2010
DOI: 10.3390/molecules15031811
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial, Cytotoxicity and Phytochemical Screening of Jordanian Plants Used in Traditional Medicine

Abstract: Antimicrobial activity and cytotoxicity of fifty one extracts of different parts of 14 plants were studied. Ethanol, methanol, aqueous, butanol, and n-hexane extracts were tested against three Gram negative, two Gram positive bacteria, and two fungi. Cytotoxicity and phytochemical screening were determined using MTT and TLC assays, respectively. Of the fifty one extracts, twenty two showed activities against different microorganisms with MICs ranging from 62.5 to 1000 µg/mL. The highest activity (100% inhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
110
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(120 citation statements)
references
References 28 publications
8
110
0
2
Order By: Relevance
“…It should be noted that MIC endpoint criteria are not consensual. In fact, some authors consider values of 250 µg/ mL as strong antibacterial activity (Aligiannis et al, 2001;Talib & Mahasneh, 2010), whereas others use a stricter endpoint criteria (Cos et al, 2006a(Cos et al, , 2006b, in which crude extracts with MIC values less than 100 µg/mL can be considered as active and are worthy for further studies. Taking into account the different criteria, extracts with a MIC value ≤125 µg/mL were considered to be active in this study.…”
Section: Chenopodium Ambrosioides L (Amaranthaceae) Kanunka Unconomentioning
confidence: 99%
“…It should be noted that MIC endpoint criteria are not consensual. In fact, some authors consider values of 250 µg/ mL as strong antibacterial activity (Aligiannis et al, 2001;Talib & Mahasneh, 2010), whereas others use a stricter endpoint criteria (Cos et al, 2006a(Cos et al, , 2006b, in which crude extracts with MIC values less than 100 µg/mL can be considered as active and are worthy for further studies. Taking into account the different criteria, extracts with a MIC value ≤125 µg/mL were considered to be active in this study.…”
Section: Chenopodium Ambrosioides L (Amaranthaceae) Kanunka Unconomentioning
confidence: 99%
“…When some Palestinian plants were tested for bioactivity, out of fifteen used in traditional medicine, only eight showed antibacterial activity against eight different bacterial strains (Essawi & Srour, 2000). Butanol extracts of Rosa damascene, Narcissus tazetta, and Inula viscose exhibited potent antimicrobial activities against different microorganism including Methicillin-resistant Staphylococcus aureus and Candida albicans (Talib & Mahasneh, 2010b).…”
Section: Plants As a Source Of Antimicrobial Agentsmentioning
confidence: 99%
“…contain a high level of phenolic compounds with a significant antioxidant capacity (VanderJagt et al, 2002). Many investigations have also revealed that roses contain a wide diversity of phenolic compounds such as gallic acid, kaempferol, rutin, myricetin, and quercetin that not only possess antioxidant activities but also exert anti-allergic, anti-inflammatory, antiatopic, antibacterial, antiviral, antifungal, antidepressant, and antistress effects (Jeon et al, 2009;Ulusoy et al, 2009;Talib and Mahasneh, 2010;Boskabady et al, 2011).…”
Section: Introductionmentioning
confidence: 99%